Optimalisasi Labview Sebagai Kendali dan Monitoring Arus Tegangan pada Modul Solar Cell Menggunakan Jaringan Lokal - Sugeng Dwi Riyanto; Purwiyanto Purwiyanto; Riyani Prima Dewi (Infotekmesin, 2023)
Renewable energy sources in Indonesia have been widely used, one of which is solar energy, for various needs, one of which is for solar power generation by using solar cells as the medium. In generating electricity, solar cells are very dependent on the intensity of the sun so as to produce currents and voltages that are not constant. Because of this, a monitoring system was created to monitor the current and voltage in a solar cell module to determine current and voltage conditions. In this study, the monitoring system used wireless data transmission via the XBee S2C module installed on the Arduino Mega 2560 and Arduino UNO. The INA 219 sensor is mounted on a solar cell module along with a relay module connected to the Arduino Mega 2560 and the XBee S2C module. The test results show that wireless data transmission cannot be used indoors at a distance of more than 20 meters. The INA 219 sensor as a reader for DC current and voltage parameters has an error rate of 0.49% to 0.75% for voltage and for DC current readings it has an error rate of 1.85%. The results of current and voltage readings are displayed on a LabVIEW interface in real-time and can be accessed via a web browser using a local network. Relay control carried out through LabVIEW has a delay time of 6.08 seconds. Logging data can be stored in .xls files and data displayed on a web browser has a delay of one to two seconds.